Pengaruh Pakan terhadap Status Fisiologi Kambing Kacang (Capra aegragus hircus) dengan Pola Pemeliharaan Insentif di Daerah Lahan Kering - Foeh, Nancy; Datta, Frans Umbu; Ndaong, Nemay; Detha, Annytha; Akal, Rocky (FAKULTAS KEDOKTERAN HEWAN UNIVERSITAS NUSA CENDANA, 2021)
The aim of this research was to determine the ratio between the provision of Moringa to the physiological status (body temperature) of female goats. This research was conducted in the dryland field laboratory of the Nusa Cendana University, using 16 adult female goats, with a range of 6-7 months and body weight ranging from 10-12 kg. Goats were divided into 2 groups, namely groups using ammoniated grass and concentrate formulations combined with Moringa and without Moringa. The results showed that the body temperature of kacang goats that placed in individual cages with incentive maintenance patterns with cage adaptation for approximately 45 days, with a feeding pattern with no moringa concentrate and with moringa that given in the morning ranged from 38.8-39.0˚C and 38.7-39.2˚C. While in the afternoon, ranging from 38.7-39.2˚C and 38.7-39.0˚C. The conclusion is this body temperature was still in the normal range of body temperature for young female kacang goats.